Company Responsibility Towards Phoneed Employees Without Getting the Rights of Severance Pay - Mhd Saiful Anwar; Germanos David; Muhammad Aldi (Return : Study of Management, Economic and Bussines, 2022)
Backgrounds: How form protection law for worker company X affected Termination Connection Work (PHK) Type research used _ is normative study law or also called research doctrinal law . aim: Knowing not quite enough answer company to cariawan phk without get severance pay _ Methods: Study this use type customized approach _ with the problem raised in study this . Findings : Obviously that priority _ in Constitution employment is justice and protection social for workers who are actor main in employment , but in reality still occur injustice social to worker , one for example is Termination Connection Work (PHK). In life daily disconnection connection work Among workers and entrepreneurs normal known with term layoff or Termination Connection Work , which can occur because has promised or promised before and can also happen because dispute Among worker with businessman , death worker or because reason another